France : Financial Sector Assessment Program-Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision for France. The assessment was completed as part of a Financial Sector Assessment Program (FSAP) undertaken by the IMF during 2012. The assessment reveals that France has a well-developed public infrastructure supporting effective banking supervision. It has a complete system of business laws, consistently enforced. Accounting standards for listed companies and other consolidated accounts have been prepared to International Financial Reporting Standards (IFRS), as adopted by the European Union.